Landscape constructions on Instagram. A postmodern reinvention of romanticism - Niklas Toresson (Digital Geography and Society)
An increasing number of people select their travel destination according to its ‘Instagrammability’. As a result, certain places emerge as ‘Instagram hotspots’, where tourists replicate the same photos, leading to a plethora of nearly identical images on Instagram. Despite Instagram's profound influence on travel behavior and landscape representations, existing research has largely focused on single case studies, with limited attention to the dominant aesthetic strategies shaping landscape representations on the platform. This article addresses this gap by examining how landscapes are constructed on Instagram and how these stereotypical portrayals reflect broader societal and ecological narratives. Employing a mixed-methods approach that combines qualitative iconographic-iconological techniques and quantitative content analysis, the study analyzes 625 landscape photographs posted by 25 German-speaking Instagram influencers, supplemented by 18 structured interviews with tourists influenced by Instagram imagery. The findings reveal that landscape pictures on Instagram echo Romantic era paintings, using similar motifs and aesthetic strategies. Instagrammers, like 19th-century Romantic painters, emphasize themes of solitude, mystification, sublimity, and nostalgia, contrasting sharply with contemporary issues like ecological crises. By staging and aesthetically transforming nature, Instagrammers medially reverse the destruction of nature and create idealized landscapes that evoke a bygone, pre-industrial era and an intact human-nature relationship. Accordingly, landscape images on Instagram can be interpreted as a new idealized, romantic reality or as a postmodern reinvention of Romanticism. Instagrammers seek out photo locations based on their ability to synthesize as many physical elements as possible into an ‘instagrammable’ scenery, creating a stereotypical romantic landscape image.